The role of work engagement in mediating the effect of job characteristics and compensation on performance - Susila, Muktar Redy (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
This study aims to analyze the effect of job characteristics and compensation on performance through work engagement. There are four variables in this study, including work engagement, compensation, job characteristics, and performance. Several previous studies have shown that work engagement is able to mediate the influence of job characteristics and compensation on performance. The data of this research comes from the perception of tax bailiff. The sample size of 263 employees was obtained by using Slovin formula. The analytical SEM PLS method was used to answer the research objectives. The results obtained from this research show that work engagement is able to mediate the effect of job characteristics and compensation on performance. In addition, the direct influence test shows that job characteristics and compensation have a significant and positive effect on work engagement. Job characteristics, compensation, and work engagement have a significant and positive effect on performance.